Power Characteristics of Wireless Charging for Sensor Networks in Tunnels - Xiaoming Liu; Enjie Ding; Duan Zhao; Youfang Yang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
In order to generate wireless microwave power charging technology in coal mine tunnels, it is necessary to know the power characteristics of wireless electromagnetic wave along the tunnel walls. In this paper, the experimental results of narrowband wireless electromagnetic wave propagation measurements are presented, and a statistical model of the power characteristics at 2.4 GHz in real rectangular mine tunnels is proposed. Two standard half-wave dipole antennas were used to perform the field experiments in tunnels with different wall materials. A 10-meter wireless charging distance belongs to the free-space propagation zone. The path loss exponents rely heavily on the location of the receiver and antenna polarizations. To obtain more power, the locations of the receiver should match the corresponding polarizations.